2020
DOI: 10.1186/s12881-020-01056-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ATP2C1 mutations in the patients of Hailey-Hailey disease

Abstract: Background: Familial benign chronic pemphigus, also known as Hailey-Hailey disease (HHD), is a clinically rare bullous Dermatosis. However the mechanism has not been clarified. The study aim to detect novel mutations in exons of ATP2C1 gene in HHD patients; to explore the possible mechnism of HHD pathogenesis by examining the expression profile of hSPCA1, miR-203, p63, Notch1 and HKII proteins in the skin lesions of HHD patients. Methods: Genomic DNA was extracted from peripheral blood of HHD patients. All exo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Interestingly, the expression of ATP2C1 was strongly downregulated in cells derived from lesional skin areas but not in cultured keratinocytes originating from unaffected skin areas of the same patients 14 . We and others also observed that keratinocytes as well as the skin tissue derived from lesional skin of HHD‐patients have a reduced expression of NOTCH1 protein 14,15,18,20 . Conversely, reducing the expression of ATP2C1 gene by siRNA‐mediated silencing, we found increased NOTCH1 expression levels 18 .…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…Interestingly, the expression of ATP2C1 was strongly downregulated in cells derived from lesional skin areas but not in cultured keratinocytes originating from unaffected skin areas of the same patients 14 . We and others also observed that keratinocytes as well as the skin tissue derived from lesional skin of HHD‐patients have a reduced expression of NOTCH1 protein 14,15,18,20 . Conversely, reducing the expression of ATP2C1 gene by siRNA‐mediated silencing, we found increased NOTCH1 expression levels 18 .…”
Section: Resultssupporting
confidence: 47%
“…14 We and others also observed that keratinocytes as well as the skin tissue derived from lesional skin of HHD-patients have a reduced expression of NOTCH1 protein. 14,15,18,20 Conversely, reducing the expression of ATP2C1 gene by siRNA-mediated silencing, we found increased NOTCH1 expression levels. 18 Thus, it could be that the discrepancy in NOTCH1 expression between siRNA-ATP2C1-treated and the lesion-derived keratinocytes underlies a differential effect on NOTCH1 activity by short-and long-term inactivation of ATP2C1 and could represent a pathogenetic mechanism of the disease manifestation.…”
Section: Canonical Ligand-dependent Pathway Involving Proteolytic Rel...mentioning
confidence: 59%
See 1 more Smart Citation
“…For the hundreds of target genes of the six upregulated miRNAs, NOTCH1, SOCS3, and BCL2 may have significant integration with the pathogenesis of PV. NOTCH1 is the shared target mRNA of miR-181a-5p and miR-326 and is a crucial mediator for the homeostasis of keratinocytes, which was found to be suppressed by miR-125b and decreased in Hailey–Hailey disease [ 29 , 30 ]. The decreased level of NOTCH1 was related to the oxidative stress of keratinocytes, which contributed to the disease activity of pemphigus vulgaris [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by ATP2C1 mutation, encoding secretory pathway Ca 2+ /Mn 2+ -ATPase 1 (SPCA1). 1 , 2 Updated on May 16, 2022, 264 public variants have been documented in ATP2C1 LOVD database ( https://databases.lovd.nl/shared/genes/ATP2C1 ). We report a sporadic case of isolated perianal Hailey-Hailey disease caused by a novel splicing mutation of ATP2C1 with Human Papillomavirus (HPV) 58 infection.…”
mentioning
confidence: 99%